Caffeine consumption within British fencing athletes - Morris, George Bowra; Manders, Ralph Johannes Francisca; Hulton, Andrew Thomas (Frontiers in Nutrition, 2022)
The ergogenic effects of caffeine are well documented, yet despite the potential benefits of supplementation, there is a lack of understanding of caffeine habits and supplementation within fencing. British fencers (n = 136) completed a Web-based questionnaire, exploring self-reported caffeine consumption, reasons for use and education. Fencers (94.4%) habitually consumed caffeine, primarily due to the taste of the products (93.8%). Respondents ingested 183.4 ± 137.5 mg of caffeine daily, with a significant difference between age groups (p < 0.01). Many respondents (53.6%) consumed caffeine 60 minutes prior/during fencing training and/or competition with the main reason highlighting cognitive performance enhancement. Respondents ingested 128.2 ± 97 mg of caffeine during training/competition, mainly as energy drinks, bars, and powders. Education on caffeine supplementation was low (25.7%), with a significant association between age groups (p < 0.05). Evidence implies ubiquitous use of caffeine in fencing, to magnify cognitive performance, and a need for education on caffeine supplementation.